Is obesity a risk factor for carotid atherosclerotic disease?—opportunistic review - Ferreira, Joana (2022)
Obesity is a risk factor for coronary atherosclerosis. However, the influence of adipose tissue in carotid atherosclerosis is not completely understood. No systematic review/meta-analysis was previously performed to understand if obesity is a risk factor for carotid atherosclerosis. This paper aims to provide an opportunistic review of the association between obesity and carotid atherosclerosis and define the role of the different adipose tissue depots in the characteristics of carotid stenosis. The databases PubMed and Cochrane Library were searched on 15–27 April and 19 May 2021. A total of 1750 articles published between 1985 and 2019 were identified, 64 were preselected, and 38 papers (35,339 subjects) were included in the final review. The most frequent methods used to determine obesity were anthropometric measures. Carotid plaque was mostly characterized by ultrasound. Overall obesity and visceral fat were not associated with the presence of carotid plaque when evaluated separately. Waist-hip ratio, however, was a significant anthropometric measure associated with the prevalence of carotid plaques. As it reflected the ratio of visceral and subcutaneous adipose tissue, the balance between these depots could impact the prevalence of carotid plaques.